Способ определения вероятности выживания кванта в дисперсных средах - Горячев Б. В. Борис Валентинович; Ларионов В. В. Виталий Васильевич; Кутлин А. П.; Могильницкий С. Б. Сергей Борисович; Савельев Б. А.
опубл. 30.04.89